Lexical-functional syntax - Bresnan, Joan; Ohio Library and Information Network (Malden, MA : Chichester, West Sussex : Wiley-Blackwell, 2016)
"Provides both an introduction to LFG and a synthesis of major theoretical developments in lexical-functional syntax over the past few decades"--
Includes bibliographical references and index
Keywords: Grammar, Comparative and general -- Syntax; Lexical-functional grammar; Electronic books